The Influence Of Competence And Communication On Work Productivity In The Interior Division Of PT Raya Azura Persada - Agustina Mogi; Muchlis Catio; Yayan Sudaryana (Journal of Management, Economic, and Accounting, 2026)
PT Raya Azura Persada as a construction company with an Interior Division faces productivity challenges in the form of project time deviations, high levels of rework, and ineffective cross-functional communication. These conditions encouraged the conduct of this study to analyze the influence of competence and communication on the work productivity of employees in the Interior Division of PT Raya Azura Persada. The research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to all employees of the Interior Division, totaling 50 respondents. Data analysis was conducted using the Partial Least Square (PLS) method with the assistance of the SmartPLS application. The results of the study indicate that, partially, competence has a positive and significant effect on work productivity. Likewise, communication also has a positive and significant effect on work productivity. Simultaneously, competence and communication were proven to have a significant effect on work productivity, with the ability to explain 67.7% of the variation in employee work productivity. These findings indicate that employee productivity in the Interior Division is determined not only by individual abilities and skills but also by the effectiveness of communication in work implementation. This study is expected to provide practical contributions for the management of PT Raya Azura Persada in formulating human resource development policies, particularly through improving employee competence and enhancing work communication systems to sustainably increase employee productivity.